Bioconvection and Hall current analysis for peristalsis of nanofluid. (December 2021) - Hayat, T.; Nisar, Z.; Alsaedi, A.
Abstract: This work develops the bioconvective peristaltic transport of nanoliquid with gyrotactic microorganisms. Channel walls are considered symmetric and elastic nature. Partial slip conditions are imposed. Nanofluid considered in this study features the impacts of Brownian motion and thermophoresis. Consequences of Hall current and thermal radiation are also examined. The governing equations in the proposed model are optimized by taking the assumption of a large wavelength and small Reynolds number. Numerical method is exploited for finding the solution of highly nonlinear differential equations. The results for velocity profile, concentration, temperature, heat transfer coefficient and density of motile microorganism profile are examined graphically. Major findings of the study are highlighted in the conclusion section.